Belief in Psychological Myths Among Students – A Comparison Between Psychology and Other Fields of Study - Adamczyk, Agata; Barakat, Hanna; Bejnar, Alicja (Przegląd Psychologiczny, 2024)
Objective: The popularization of unscientific content is becoming increasingly prevalent in the era of global internet access. Identifying and debunking psychological myths should be an essential part of the education of individuals training to become psychologists. This study examined whether there are differences in the identification of psychological myths between psychology students and students from other fields. Method: The study included 331 participants, consisting of 132 psychology students and 199 students from other disciplines. A questionnaire based on the work of Lilienfeld et al. (2017) was used to measure belief in psychological myths. The questionnaire consisted of 17 statements - 10 myths and 7 facts - which participants assessed for their validity through an online survey. Data were analyzed using independent samples t-tests. Results: Respondents’ answers indicated a small difference in the average number of correct responses between psychology students and students from other fields, with a moderate effect size. Conclusion: The results confirmed the hypothesis that psychology students are less likely to believe in psychological myths. However, the study also revealed that the incorrect identification of popular psychological myths is common among young people, indicating a need for educational intervention.